Isolamento e caracterização bioquímica e biológica de um peptídeo antimicrobiano extraído da peçonha do escorpião Tityus obscurus Gervais 1843 (Scorpiones Buthidae) - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2017)
Scorpion venoms are sources of bioactive molecules such as Antimicrobial Peptides (AMPs), which are innate immunity molecules and found in the animal and plant kingdoms. In this work, it was purified and characterized a novel AMP from the venom of the Amazonian scorpion Tityus obscurus. Animals were collected in the Tapajós National Forest, West region of Pará state, Brazil. The venom was extracted by electrostimulation technique, using a variable power supply. Molecular mass distribution in the venom was assessed running 15% SDS-PAGE. Purification of an antimicrobial peptide (P42) migrating at 42 min was done by High-Performance Liquid Chromatography (HPLC). For biological characterization, antimicrobial activity on the Gram-negative Escherichia coli, Gram-positive Staphylococcus aureus bacteria and fungi Candida albicans, C. tropicalis and C. parapsilosis were performed using the standard methods of disk diffusion sensitivity and Minimum Inhibitory Concentration (MIC) of the Clinical and Laboratory Standards Institute (CLSI) for bacteria (M2A-9 standard) and fungi (M44-A and M27-A2 standards). Additionally, mouse membrane hemolytic effect of the purified P42 was determined, as well as monitoring of the kinetic cytotoxicity by confocal microscopy images. The results of mass-spectrometric analysis showed a m/z ratio of 7284.4 Da and N-terminal amino acid sequence of the first 30 residues of the peptide determined by Edman degradation, which has a 97% identity with the previously reported nucleotide sequence of To4 precursor from T. obscurus. P42 was only active against fungi. MIC values against Candida species were 3.5-7.0 μM, compared to fluconazole 6.0-12.0 mM and it did not show hemolytic effect in mouse erythrocyte. These results report, for the first time, the purification and characterization of a native AMP from the venom of the Amazonian scorpion T. obscurus. This kind of biological molecules constitutes a novel approach to drug development, especially against multidrug-resistant pathogens.
Keywords: Candida albicans; Peptídeo antimicrobiano; Tityus obscurus; CNPQ::CIÊNCIAS EXATAS E DA TERRA; ESTUDOS E MANEJOS DE ECOSSISTEMAS AMAZÔNICOS